Scandal, Social Policy and Social Welfare. - Butler, Professor Ian (Policy Press, 2005)
This book, by examining the landmark scandals of the post-war period, including more recent ones, such as the Victoria Climbie Inquiry, reveals how scandals are generated, to what purposes they are used and whose interests they are made to serve.